IMPACT FACTOR: DOES IT HAVE AN IMPACT? - Manzar, N; Manzar, B; Manzar, S (Journal of Ayub Medical College Abbottabad, 2009)
Editor, The journal's impact factor is at present, considered a yard stick for measuring the relative quality and significance of a journal. It is defined as the frequency with which the '˜average article' in a journal has been cited in a particular year or period.1 For a given year, this is calculated as the total number of citations received in that year to articles published in the previous two years divided by the total number of citable items published by the journal in the same two years. The Impact Factor was devised by and is calculated by The Institute for Scientific Information® (ISI®), now known as '˜Thomson Scientific'. Unfortunately as stated by Dr. Abbasi in BMJ 2004, ISI® only follows about 5% of over 130,000 known medical and scientific journals published annually. Moreover, the citation ranking invented by Eugene Garfield is scientifically meaningless as is established by indisputable evidence and even the inventor for a long time has warned people not to trust impact factor for solely judging the quality of a journal and in an article has termed its usage as '˜dangerous'.2 Despite the realisation on a global scale that impact factors are a faulty system of assessment of a journal3, we tend to agree with Hoeffel4 that '˜impact Factor is not a perfect tool to measure the quality of articles but there is nothing better and it has the advantage of already being in existence and is, therefore, a good technique for scientific evaluation. Even today career advancement, getting funding and grants all depends on how many articles one has published in journals with good impact factors. With increased awareness about impact factors and their potential impact on career growth and international recognition many researchers are now targeting international indexed journals with good impact factors. The number of publications from Pakistan in international indexed journals with impact factors arose by about 179% from 1992 to 2002 reflecting the change in this trend.5 In this dim scenario the local non-indexed medical journals face a serious challenge. They will have to work hard towards sustained improvement of the journal from submission to publication as the time, as yet has not come to ignore the numbers. This will ultimately have huge implications for evidence based medicine in third world countries especially Pakistan where local journals provide good evidence comparable to international standards.